TINJAUAN SISTEMATIS PROGRAM ELSA (EMOTIONAL LITERACY SUPPORT ASSISTANT): POTENSI ADAPTASI PADA PENDIDIKAN DASAR DI INDONESIA - Andini Amalia Putri Nasrulloh; Seni Apriliya (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the Emotional Literacy Support Assistant (ELSA) programme as a school-based intervention in strengthening students’ emotional literacy in primary schools, as well as its potential adaptation within the context of primary education in Indonesia. The research employed a Systematic Literature Review with a descriptive qualitative approach. The findings indicate that the programme contributes positively to students’ ability to develop emotional literacy. However, its implementation faces several challenges. Overall, the programme is considered relevant to the Indonesian primary education context, yet it requires contextual adaptation, strengthening of human resources, and integration into school culture in order to be implemented effectively and sustainably. Keywords: emotional literacy, primary education, school-based intervention